Digital Pop Up Book Media Based on Balinese Art Craft Entrepreneurship for Grade V Elementary School - Ni Komang Sri Rahayu Juwita Sari; Anak Agung Gede Agung; I Made Citra Wibawa (Jurnal Pendidikan Multikultural Indonesia, 2025)
Economic Elementary economic learning tends to be theoretical, less contextual, and insufficiently supported by innovative technology-based media, resulting in low conceptual understanding and student learning interest. In addition, the early development of entrepreneurial awareness remains suboptimal due to limited instructional media that connect economic concepts with students’ real-life experiences. This study aims to analyze, develop, and evaluate the effectiveness of a digital pop-up book based on entrepreneurship to enhance students’ economic conceptual understanding and foster entrepreneurial awareness. This research employed a development research design using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects involved 20 elementary school students. Data were collected through observations, interviews, questionnaires, and multiple-choice tests using validated instruments. Data were analyzed using descriptive quantitative and qualitative techniques and a paired-sample t-test. The results indicate that the developed media met the criteria of validity, practicality, and effectiveness. The implementation of the digital pop-up book significantly improved students’ economic conceptual understanding, learning interest, and entrepreneurial awareness. These findings imply that digital learning media integrating local cultural contexts can serve as innovative instructional tools to support technology integration, strengthen economic literacy, and promote entrepreneurship education in 21st-century learning.